The Impact of Negative Campaign and Shock Advertising on Consumer Trust and Purchase Intention toward Local and Imported Skincare Brands in Indonesia - Bradley Pangestu; Agustina Intan Setioningsih; Ahmad Fairuz Nafi; Bagas Santoso; Diva Varella Septylo; Muhammad Fhazil Alifa (FEB Universitas Mulawarman, 2025)
Abstract The skincare industry has attracted a lot of interest. Despite its positive aspects, the skincare industry faces serious reputational challenges, one of which is the practice of negative campaigns against local brands. Therefore, this paper aims to analyze the influence of negative campaigns and shock advertising on consumer trust and purchase intention towards local and imported skincare brands in Indonesia, the scientists have proved those marketing techniques had influenced customers behavior. The research method used is a quantitative approach with data collection through an online questionnaire to people who are currently using local and imported skincare products specially at the Faculty of Economics and Business, Mulawarman University. A Likert scale of 1–5 was applied to measure respondents' perceptions of the research variables: negative campaigns, shock advertising, consumer trust, and purchase intention, to know the impact of those variables to customers behavior. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to test direct relationships, mediation effects, and moderation. The hypothesis proposed in this PLS-SEM model confirms that (a) Negative Campaign (NC) has negative impact on Consumer Trust (CT) and Purchase Intention (PI); (b) Shock advertising (SA) affects Consumer Trust (CT) negatively but affects positively on Purchase Intention (PI); and (c) Consumer Trust (CT) has a positive impact on Purchase Intention (PI).